Analisis pembelajaran intrakurikuler dalam pelaksanaan kurikulum merdeka di kelas iv sekolah dasar - Muhammad Miftahudin Afif; Hasan Mahfud; Roy Ardiansyah (Universitas Sebelas Maret, 2023)
The purpose of this research is to describe intracurricular learning in implementing Independent Curriculum in class IV Elementary School. This research used qualitative approach with case study method. The subjects in this research were fourth grade students, fourth grade teachers, and the principal. This research used purposive sampling. Data collection techniques were interviews, observation, and document studies. Data validity testing technique used data source triangulation and technical triangulation. Data analysis technique used interactive analysis by Miles and Huberman, namely by collecting data, reducing data, displaying data, and drawing conclusions or verification. The results of this research are planning, there is learning purpose flow planning, graduate planning and assessment, use and development of educational equipment. Whereas, for the implementation of the training has done application of students centered learning, combination of assessment in learning, learning according to the level of learning of students, collaboration between teachers for the purposes of curriculum and learning. However, collaboration with parents and the community does not contribute optimally to the learning process. Reflection, evaluation and improvement of quality implementation of curriculum are also carried out.